Pengaruh Kepemimpinan, Kompensasi dan Disiplin Kerja Terhadap Kinerja Karyawan - Ramli Ramli; Aryati Arfah; Muhammad Arif (Jurnal Ilmiah Multidisiplin Amsir, 2023)
This study aims to explain the effect of job satisfaction, organizational commitment, and employee competence on employee performance in the Balo'ta Savings and Loan Cooperative in the South Sulawesi region. This type of research is quantitative. The population in this study are KSP employees. Balo'ta for the South-Sulawesi region by taking on eight branch offices totaling 45 employees. Data collection used a sampling technique, namely saturated sampling which was distributed to 45 respondents. The method used is multiple linear regression, with the help of SPSS 24 software. The results of this study indicate that the effect of job satisfaction, organizational commitment has a significant effect on employee performance, while employee competency does not have a significant effect on employee performance. The effect of job satisfaction, organizational commitment and employee competency on employee performance simultaneously has a significant effect on employee performance. Employee performance as indicated by a significant level of f count> f table (F count 14.441 > F table 2.85) with a significant level of 0.000, a significant level of <0.05 Test